Resonant frequency analysis of dental implants. (April 2019) - Rittel, D.; Dorogoy, A.; Haïat, G.; Shemtov-Yona, K.
Highlights: A finite element model of resonant frequency analysis of dental implants. Peri-implant interface of varying stiffness and thickness to mimic bone remodeling. Sensitivity analysis of the RFA. Results show an increased sensitivity for wider and softer peri-implant layers. Upon peri-implant bone stiffening, the sensitivity of RFA decreases rapidly. Abstract: Dental implant stability influences the decision on the determination of the duration between implant insertion and loading. This work investigates the resonant frequency analysis by means of a numerical model. The investigation is done numerically through the determination of the eigenfrequencies and performing steady state response analyses using a commercial finite element package. A peri-implant interface, of simultaneously varying stiffness, density and layer thickness is introduced in the numerical 3D model in order to probe the sensitivity of the eigenfrequencies and steady state response to an evolving weakened layer, in an attempt to identify the bone reconstruction around the implant. For the first two modes, the resonant frequency is somewhat insensitive to the healing process, unless the weakened layer is rather large and compliant, like in the very early stages of the implantation. A "Normalized Healing Factor" is devised in the spirit of the Implant Stability Quotient, which can identify the healing process especially at the early stages after implantation. The sensitivity of the resonant frequency analysis to changes of mechanical properties of periprosthetic bone tissue seems relatively weak. Another indicator considering the amplitude as well as the resonance frequency might be more adapted to bone healing estimations. However, these results need to be verified experimentally as well as clinically.